State-religion Relations and Azerbaijani Model - Gurbanlı, Mubariz (Scholarya Demo Journal of Ruby, 2019)
The progress of global events showcase that religion has become one of the leading factors of the 21st century compared to the 20th century. Today, muchdepends on the forms and methods of interaction of states with religious organizations: ensuring security within the country and in the the world, resolving conflicts on religious grounds, not being persecuted for religious affiliation or respect for freedom of conscience, etc.           This article is devoted to the state policy in the field of religion in the modern world and state-religious relations. The author notes that in modern scientific literature intensive debates on the forms of state-religion relations are carried out. While researchers of this field classify state-religion relationships, they usually focus on state's attitude towards religion by referring to a liberal-democratic tradition. According to the author, this classification covers various options such as the form where religion is dominant in the state or societies in which prevails state’s religious intolerance. The article states that the place of religion in the state system isdetermined by the constitutional structure of that state. However, in the typology ofthe model of state-religion relations, along with the constitutional structure, the type of political regime, its historical path, as well as the religious affiliation of the majority of population play an important role. From this point of view the article which deals with the experience of the the ocratic, secular and atheistic states and states that have official religion, discusses the state-religion policy pursued by Azerbaijan, as well. In particular, the historical path of the development of our country and its success in this direction is mentioned in the article.